EFFECTS OF ARTIFICIAL DIETS ON THE BIOLOGICAL CYCLE OF Condylorrhiza vestigialis - Chirinzane, Cacilda João; Sousa, Nilton José; Rezende, Eduardo Henrique; Batista, Antonio Carlos; Giongo, Marcos; Mendonça, Veruza Cristina (Floresta, 2020)
The objective of this work was to determine the influence of different artificial diets on biological parameters related to the life cycle of C Condylorrhiza vestigialis aiming to determine the most suitable diet for the rearing of a population of this insect. Four diet formulations were tested. Ten repetitions were used, with 30 caterpillars per repetition. All stages of C. vestigialis life cycle were followed to evaluate biological parameters: viability of larvae, pre pupa, pupa and adults, as well as the sex ratio. The number of larval instars, the pupal mass and the total number of eggs per day and per female day were also calculated. The four diets tested allowed the development of C. vestigialis caterpillars. All diets were considered adequate for the purpose of the work, which is the production of baculovirus used in the control program of this pest. It was the diet 2 that provided the best results, the largest pupal mass, and the quantity and viability of the eggs produced by C. vestigialis females fed in this larval phase.